2021
DOI: 10.35675/befdergi.747319
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Podcasts on Listening Comprehension and Listening Anxiety in Teaching Turkish as a Foreign Language

Abstract: Bu çalışma birinci yazarın ikinci yazar danışmanlığında hazırladığı "Yabancı dil olarak Türkçe öğretiminde elektronik dinletilerin dinlediğini anlama başarısı ve dinleme kaygısına etkisi" başlıklı doktora tezinden hazırlanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Yilmaz and Babacan (2015) investigated podcast applications aimed at improving listening skills in teaching Turkish as a foreign language and found that they enriched students' listening skills and the process of teaching Turkish as a foreign language. In addition, in a study conducted with a view to increasing the listening comprehension success of students learning Turkish as a foreign language and reducing their listening anxiety, Berk and Açik (2021) concluded that e-audience-based activities increased the success of listening comprehension.…”
Section: Three Variables Of the Research In The Context Of Teaching T...mentioning
confidence: 99%
“…Yilmaz and Babacan (2015) investigated podcast applications aimed at improving listening skills in teaching Turkish as a foreign language and found that they enriched students' listening skills and the process of teaching Turkish as a foreign language. In addition, in a study conducted with a view to increasing the listening comprehension success of students learning Turkish as a foreign language and reducing their listening anxiety, Berk and Açik (2021) concluded that e-audience-based activities increased the success of listening comprehension.…”
Section: Three Variables Of the Research In The Context Of Teaching T...mentioning
confidence: 99%
“…Türkçe öğretimi alanında gerçekleştirilen çalışmalara bakıldığında farklı öğrenim kademelerindeki öğrencilerin dinleme kaygılarını (Arslan, 2017;Ateş, 2018;Berk, 2019;Maden ve Durukan, 2016), konuşma kaygılarını (Kavruk ve Deniz, 2015;Kuru, 2018;Sallabaş, 2012;Sevim ve Gedik, 2014), okuma kaygılarını (Altunkaya, 2017;Bağcı ve Baz, 2019;Kuşdemir ve Katrancı, 2016;Şahin, 2019) ve yazma kaygılarını (Ateş ve Akaydın, 2015;Karakoç Öztürk, 2016;Kılıç ve Arslan, 2018;Ürün Karahan, 2017) ortaya koyan çeşitli araştırmalar mevcuttur. Ancak Türkçe öğretiminde kaygı üzerine yapılan araştırmaları bütüncül bir şekilde ele alıp inceleyen, bu alandaki araştırmaların eğilimlerini tespit eden bir araştırmanın olmadığı da görülmektedir.…”
Section: Kemiksizunclassified
“…Açık and Berk (2021) share findings indicating that the use of podcasts in teaching Turkish as a foreign language reduces listening anxiety. In broader studies on the use of podcasts for language instruction, it has been noted that podcasts not only enhance listening but also lead to significant improvements in grammar, speaking, pronunciation, and vocabulary areas for students (Chan et al, 2011;Kaplan-Leiserson, 2005).…”
Section: Introductionmentioning
confidence: 99%